skeeter MHF Helper Jun 2008 16,216 6,764 North Texas May 15, 2010 #2 johntricklebank said: solve for x log4(5-2x)=3 log5(8x)-log5(3)=log5(x+10) Click to expand... \(\displaystyle \log_4(5-2x) = 3\) change to an exponential equation ... \(\displaystyle 4^3 = 5-2x\) finish \(\displaystyle \log_5(8x)-\log_5(3)=\log_5(x+10)\) combine logs on the left using the log difference property ... \(\displaystyle \log_5\left(\frac{8x}{3}\right) = \log_5(x+10)\) \(\displaystyle \frac{8x}{3} = x+10\) finish
johntricklebank said: solve for x log4(5-2x)=3 log5(8x)-log5(3)=log5(x+10) Click to expand... \(\displaystyle \log_4(5-2x) = 3\) change to an exponential equation ... \(\displaystyle 4^3 = 5-2x\) finish \(\displaystyle \log_5(8x)-\log_5(3)=\log_5(x+10)\) combine logs on the left using the log difference property ... \(\displaystyle \log_5\left(\frac{8x}{3}\right) = \log_5(x+10)\) \(\displaystyle \frac{8x}{3} = x+10\) finish